2003
DOI: 10.1002/pds.831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors associated with prescription of a potentially inappropriate combination dermatological medication among US outpatient physicians

Abstract: The increased risk of potentially inappropriate prescription of clotrimazole/betamethasone diproprionate by physicians across all specialties and increased probability of medication receipt in racial minorities is of concern, when safer alternatives such as antifungals or anti-inflammatory medications without the side effects of the combination medication are easily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This may be due to a limited prescription drug coverage offered to Medicare benefi ciaries 34 . The research has also documented that the type of insurance coverage has a signifi cant impact on the prescription of pharmacotherapy 36 . Furthermore, some of the newer non-benzodiazepines are expensive compared with the generic version of older benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a limited prescription drug coverage offered to Medicare benefi ciaries 34 . The research has also documented that the type of insurance coverage has a signifi cant impact on the prescription of pharmacotherapy 36 . Furthermore, some of the newer non-benzodiazepines are expensive compared with the generic version of older benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has indicated that 20-36% of patients in PCP offices have dermatologic conditions 1. PCPs have been shown to prescribe inappropriately high-potency topical corticosteroids (TCS), or, conversely, inappropriately low-potency TCS. 2 In addition, drug costs may be higher if multiple small tubes are dispensed over the treatment course. 3 Importantly, mobile devices and applications provide significantly increased access to point-of-care tools and, with use by providers, demonstrate better clinical decision-making and improved patient outcomes.…”
mentioning
confidence: 99%
“…Our group has used clotrimazolebetamethasone dipropionate prescribing behavior as a measure of the quality of dermatologic services provided by practitioners in different specialties. 3,4 Herein, to assess the quality of dermatologic care provided by physician assistants, we analyze clotrimazole-betamethasone prescribing behavior of 4 practitioner groups: dermatologists, dermatology physician assistants, primary care providers, and primary care physician assistants.…”
mentioning
confidence: 99%
“…Data on the use of the combination antifungal agent clotrimazole-betamethasone were obtained from the 1995-2004 National Ambulatory Medical Care Survey 5 and analyzed as previously described. 3,4 First, we identified the 5 most common diagnoses that were treated with clotrimazole-betamethasone at least some of the time. Then we determined the percentage of visits for those 5 conditions at which clotrimazole-betamethasone was prescribed.…”
mentioning
confidence: 99%